2005
DOI: 10.2174/1389557053402864
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of Furoxans and Benzofuroxans: Recent Developments

Abstract: The chemistry of furoxans (1, 2, 5-oxadiazole-2-oxides) and benzofuroxans (benzo[1, 2-c]1, 2, 5-oxadiazole-1-oxides) is very well known. These systems are widely used in organic chemistry as intermediate compounds for the synthesis of numerous heterocycles. In the other hand, furoxan and benzofuroxan derivatives were extensively studied as bioactive compounds. They possess remarkable biological activities, such as anti-microbial and anti-parasitic properties, mutagenic, immunosuppressive and anticancer effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
72
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(73 citation statements)
references
References 0 publications
0
72
0
1
Order By: Relevance
“…In this work, tamibarotene was used as a basic model drug to be coupled with furoxans, which are NO donors that display remarkable antitumor activities (Wang et al, 2002;Cerecetto et al, 2005;Huerta et al, 2008;Hirst et al, 2010), to synthesize a new compound named QT-011. QT-011 was proposed to exert synergistic effects at multiple target sites and significantly enhance efficacy by releasing NO and tamibarotene through in vivo metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, tamibarotene was used as a basic model drug to be coupled with furoxans, which are NO donors that display remarkable antitumor activities (Wang et al, 2002;Cerecetto et al, 2005;Huerta et al, 2008;Hirst et al, 2010), to synthesize a new compound named QT-011. QT-011 was proposed to exert synergistic effects at multiple target sites and significantly enhance efficacy by releasing NO and tamibarotene through in vivo metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The thiol group or thiolate that might be generated in the reaction medium interacted with the furoxan ring, resulting in the occurrence of side reactions. 16,17 The synthetic experiment involving thiol-containing furoxans required careful handling to maintain oxygen-free, neutral conditions. Thus, the liberation of a thiol group was planned at the end of the synthetic route.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5-oxadiazole N-oxides (furoxans) are reported (11) to be thiol dependent NO donors, whose biological activity is produced by action on the soluble guanylate cyclase--cyclic guanosine monophosphate (sGC-cGMP) pathway. Furoxans are considered to possess favorable bioactivity since they cause a slow release of NO resulting in longer duration of action without development of tolerance.…”
mentioning
confidence: 99%
“…Granik and Grigor (12) proposed the mechanism for the release of NO from 1,2,5-oxadiazole N-oxides. It is also reported that release of NO from a nitric oxide donor drug produces beneficial effects such as reduction in blood pressure and prevention of atherosclerosis (11). NSAIDs possessing nitric oxide releasing capabilities are considered to be more promising drugs than the coxibs as these would be devoid of potential cardiovascular side effects associated with coxibs (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation